A stretchable and rapidly self-healable polysiloxane elastomer based on reversible aluminum–amino coordination. (31st October 2019) - Lei, Yufeng; Huang, Qiuping; Shan, Shijie; Lin, Yaling; Zhang, Anqiang
Abstract : Dynamic coordination between aluminum and amines promotes rapid self-healing for polysiloxane elastomers at lower temperature. Abstract : Self-healing polymers have been increasingly investigated for the development of sustainable materials. However, it is challenging for self-healable systems to achieve a rapid self-healing at low temperature. Here, we sought to introduce weaker yet more dynamic supramolecular interactions to construct self-healable elastomers. By incorporating main-group aluminum ions into an amino-grafted polysiloxane matrix, a supramolecular elastomer, PDMS-NH2 -Al, was obtained. Unlike most reported strong coordination systems based on transition/rare-earth metals and π-acid ligands, the coordination between main-group Al 3+ and simple σ ligands (amines) was revealed to be comparatively weaker yet more dynamic. This unique combination led to an excellent healing efficiency over 90% in 60 min even at a temperature as low as −20 °C.